Diferentes fases clínicas da DPOC: investigação da estrutura e função cardíacas e capacidade de exercício - Pereira, Mariana Brasil da Cunha Martino (Universidade Federal de São Carlos, 2020)
Introduction: Chronic obstructive pulmonary disease (COPD) is characterized by airflow obstruction and chronic airway inflammation. In addition to lung damage, COPD has several systemic consequences including impairment cardiovascular and functional. Commonly, this disease results in hospitalization in periods known as exacerbations that impact even more negatively on the health of this population, including an increased risk for cardiovascular events. However, little is known about cardiac structure and function in newly exacerbated and stable patients and their possible relationship with exercise capacity. Objectives: To assess cardiac structure and function in patients with stable COPD and recent exacerbation and their relationship with exercise capacity. Methods: Observational and cross-sectional study. The sample consisted of 40 individuals with COPD distributed in groups: 1) COPD recently exacerbated (30 days) (GEX n = 20) and, COPD clinically stable for at least three months (GEST = 20). For cardiovascular evaluation, the Doppler echocardiogram was performed and the diameter of the aorta, diameter of the left atrium, diastolic and systolic diameters of the left ventricle (LV), thickness of the interventricular septum, thickness of the posterior wall (PP) of the LV, diameter of the right ventricle (RV) were considered. ) and volumes of the left and right atria; additionally, measurements were taken regarding the function of the LV and the RV (E, A and S waves, in addition to the E / A and E / e 'relationships). Then, the six-minute walk test (6MWT) was performed and the distance walked (SD) was considered to assess exercise capacity Results: In the comparison between stable and exacerbated patients, no significant difference was observed for cardiac function and structure assessed by Doppler echocardiogram. We observed that there was a positive correlation between mitral E / A and DP on the 6MWT (r = 0.50; p = 0.001), and a negative correlation between PP of the LV and SD on the 6MWT (r = -0.33; p = 0.035). Conclusion: Cardiac function and structure were similar between the groups evaluated at different clinical stages of COPD and exercise capacity is associated with cardiac structure and function regardless of whether patients are stable or recently exacerbated.
Different clinical stages of COPD: investigation of cardiac structure and function and exercise capacity
Keywords: DPOC; COPD; Ecodopplercardiograma; Ecodopplercardiogram; Teste de caminhada; Walking test; Pneumologia; Pneumology; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL